Mixed precious-group metal–organic frameworks: a case study of the HKUST-1 analogue [RuxRh3−x(BTC)2]. Issue 32 (25th June 2019) - Heinz, Werner R.; Kratky, Tim; Drees, Markus; Wimmer, Andreas; Tomanec, Ondřej; Günther, Sebastian; Schuster, Michael; Fischer, Roland A.
Abstract : Mixed precious-group metal–organic frameworks [Ru x Rh3− x (BTC)2 ] of the HKUST-1-type were synthesized and characterized (PXRD, BET, IR, Raman, XPS, TGA, SS-UV/VIS, EA, and HR-TEM). Abstract : This work presents the first full series of mixed precious-group metal–organic frameworks (MPG-MOFs) using ruthenium and rhodium. The obtained crystalline, highly porous and thermally robust materials were characterized by means of powder X-ray diffraction, N2 /CO2 sorption isotherms, thermogravimetry, spectroscopy methods (IR, Raman, UV/VIS-, NMR and XPS) and as well by high resolution transmission electron microscopy (HR-TEM) with elemental mapping (HAADF-EDS). Additionally, the assignment of spectroscopic data is supported by computational (time dependent)-density functional theory methods. The materials turned out to consist of homogeneously dispersed Ru2 and Rh2 paddlewheel units being linked by benzenetricarboxylate (BTC) to yield a framework that is isoreticular to [Cu3 (BTC)2 ] (HKUST-1, Hong Kong University of Science and Technology). However, acetate (OAc) is incorporated as an intrinsic component which compensates for missing BTC-linker defects and some Cl is coordinated to the Ru centre at an apical position. The exact empirical formula of the MPG-MOFs is derived as [Ru x Rh3− x (BTC)2− a (OAc) b (Cl) c ].